Efeitos da doença periodontal na gestação e sua repercussão no desenvolvimento de asma na prole: papel da fotobiomodulação - Rehim, Hassan Mohamed Mohamed Abdel (2018)
Oral cavity pathogens appear to play an important role systemically, facilitating and /or modulating the development of many diseases. Periodontal disease (PD) is consider the most common localized and inflammatory dental disease caused by bacterial infection associated with dental plaque. PD is associated with several pathological conditions, such as inflammation of the gingiva (gingivitis), degeneration of the periodontal ligament, dental cementum and alveolar bone loss. Clinical evidence shows an association between maternal DP and adverse outcomes during pregnancy, especially preterm births and low birth weight. Thus, the objective of this study was to investigate the impact of PD on the development of asthma in the offspring, as well as the role of photodynamic therapy (PDT). For this, we used Wistar rats submitted to PD induction by ligation in the lower molar teeth and posterior mating. The treatment with PDT was performed 14 days after the establishment of PD. After 30 days of birth, the offspring was sensitized and challenged with ovalbumin for the induction of experimental asthma. The studies prioritized maternal and offspring analyzes. With respect to the mothers we noticed that the DP increased the leukocytes in the blood, did not alter the weight gained during the gestation, on the other hand caused premature birth. In relation to pups, PD caused low birth weight and suppressed the tracheal hyperreactivity without altering the lung cellularity. PDT treatment in rats with PD suppressed the development of asthma in the offspring by reducing the cells migrated to BAL and not altering the reduced tracheal reactivity. Thus, our data show that PD interferes in the immune system of the offspring by modifying an inflammatory response of allergic origin, which at first time, seems to have a protective effect. Thus, studies aimed at investigating the systemic impact of PD, especially in the uterine microenvironment and its effects on the immune system of the offspring are relevant.